Clay Mineral Identification for the Utilization of the Brick Industry in Bukit Raya, Tenggarong Seberang, Kutai Kartanegara - Raharjanti, Ni'matul Azizah; Agustina, Fitriyati; Anggraeni, Sarah (Fakultas Teknik Geologi Universitas Padjadjaran, 2024)
Bricks as one of the main components in buildings are often made by clay contained material that supplied from the nearby resources, including in Bukit Raya, Tenggarong Seberang, Kutai Kartanegara. However, the type of clay minerals that utilized for the brick in the research area, is not identified in detailed analysis. The research is conducted to identify the lithology of the brick material as well as the clay mineral that consists in the soil or material. The analysis is carried out through field observation and laboratory analysis which included X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), and X-Ray Fluorescence (XRF) analysis. The analysis resulting the lithology of the research area is predominantly sandstone alternating with claystone and coal intercalation. The XRD analysis on claystone and soil that used for bricks showing that the samples are mainly composed by quartz, with clay minerals identified is kaolinite, montmorillonite, and illite. However, according to the SEM analysis, only kaolinite and montmorillonite that present in the samples. According to the geochemistry of the samples, the average SiO2 content is ranging from 45.8% to 55.50%. The Fe2O3 content is measured from 2.02% to 5.96% which excess the SNI standard for pottery that set as 0.8 wt.%. CaO component varying from 0.117 to 0.221 wt.%, which still in the allowed value for the pottery materials which set to maximum 1 wt%.